Numerical analysis of soft clay reinforced with stone columns - Alkhorshid, Nima Rostami (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: Soft clays usually exist in many coastal areas and they reveal high Compressibility and poor strength. There are various methods for improving in situ conditions of soft clays. Among these methods, stone columns are considered to be the most advantageous and cost-effective ground modification techniques. Stone columns are widely used to reduce the settlement of soft clays, accelerate the rate of consolidation by reducing the length of the drainage path and increase the load bearing capacity. Among the other ground modification techniques, stone column is simple to apply. Stone column application replaces the soft soil by a stronger material and mitigates the potential for cyclic mobility by accelerating the dissipation of excess pore pressure during earthquakes. The aim of this study was to investigate the performance of stone columns in soft compressible clay. For this reason, finite element analyses were carried out to evaluate settlement of soft clay reinforced with stone and encased sand columns. Sand columns were considered to be encased using geotextiles. 15-noded triangular elements using Plaxis software were used for the analysis. A drained analysis for stones and sand columns was carried out using Mohr-Coulomb’s criterion whereas for soft clay undrained analysis was performed. The modeling of sand and stone columns was designed by axisymmetric pattern in Plaxis. In the study, the excess pore water pressure, settlement and the consolidation rate of the natural, sand and stone column reinforced soft cohesive soil under static and dynamic loading were analyzed using different column diameters. The bulging failure and the vertical settlement of the stone and the sand columns in the presence and absence of dynamic loading were analyzed and discussed. Results of the analyses indicated that the main factor influencing the value of maximum bulging is the amount of the axial load applied on the stone columns. Excessive bulging of the stone and sand columns under the applied axial loading occurred in depth of 2 to 3 times of the diameter of the stone and sand columns. Thus, the depth of bulging was related to the diameter of stone and sand columns. In the study, the finite element analysis for three-dimensional full scale modeling was also studied. In full scale three-dimensional, 3D finite element analysis, the bulging failure, punching failure and the vertical settlement of stone columns were analyzed and results were discussed. The results of the analysis indicated that the stone columns closer to the axis of symmetry gave maximum value of vertical settlement. The punching failure of the stone columns increased with the increase in the applied loading. In three-dimensional analysis of full scale clay deposits reinforced by stone columns, the maximum value of bulging occurred at a depth of three times of the diameter of stone columns. ………………………………………………………………………………………………………………………………………………………………………………………………………… OZ: Yumuşak killer genelde kıyı bölgelerinde bulunurlar ve yüksek sıkışabilirlik ve düşük mukavemet değerlerine sahiptirler. Yumuşak killeri iyileştirmek için değişik yöntemler mevcuttur. Bu yöntemler arasında en avantajlı ve ekonomik iyileştirme yönteminin taş kolonlar olduğu düşünülmektedir. Taş kolonlar yumuşak kildeki oturmaları azaltmak, drenaj yolunu kısaltarak konsolidasyon oranını hızlandırmak ve zeminin yük taşıma kapasitesini artırmak maksadı ile kullanılmaktadır. Diğer zemin iyileştirme yöntemleri arasında, taş kolonlar daha kolay uygulanabilmektedir. Taş kolon uygulaması yumuşak kilin daha güçlü bir malzeme ile yer değiştirerek deprem anında aşırı boşluk suyu basıncının çıkışını hızlandırarak zeminin sıvılaşma özelliğini iyileştirmektir. Bu çalışmanın amacı yumuşak sıkışabilir kilde taş kolon performansının araştırılmasıdır. Bu nedenle, sonsuz eleman analiz yöntemi kullanılarak, taş kolon ve kum kolonlarla güçlendirilmiş yumuşak kilin oturmaları değerlendirilmiştir. Kum kolonların geotekstil ile çevrelendirildikleri düşünülmüştür. 15-düğümlü üçgen elemanlarla Plaxis programı kullanılarak analizler yapılmıştır. Taş kolonlar ve kum kolonlar için Mohr-Coulomb kriterleri kullanılarak drenajlı bir analiz, yumuşak kil içinse drenajsız analiz gerçekleştirilmiştir. Kum ve taş kolon modellemesi Plaxis programında aksimetrik şablon kullanılarak tasarlanmıştır. Bu çalışmada, doğal, kum ve taş kolonla güçlendirilmiş yumuşak kohezyonlu zeminin aşırı boşluk suyu basıncı, oturma ve konsolidasyon oranı statik ve dinamik yükler altında değişik kolon çaplarında analiz edilmiştir. Taş ve kum kolonların kabarma göçmesi ve dikey yöndeki oturmaları statik ve dinamik yükler altında analiz edilip, tartışılmıştır. Analiz neticeleri göstermiştir kimaksimum kabarma göçmesine etki eden en önemli faktör taş kolon üzerine uygulanan dikey yüklerdir. Taş ve kum kolonlarda dikey yükler altında meydana gelen aşırı kabarma taş ve kum kolonların çapının 2-3 katı derinlikte meydana gelmektedir. Böylelikle, kabarma derinliği taş ve kum kolonların çapı ile ilişkilendirilmiştir. Bu çalışmada sonlu eleman analizi üç boyutlu tam ölçek model için de çalışılmıştır. Tam ölçekli üç boyutlu 3D sonlu eleman analizinde, taş kolonların kabarma göçmesi, zımbalama göçmesi ve dikey yöndeki oturma analizleri yapılmış ve tartışılmıştır. Analiz neticeleri göstermiştir ki simetri eksenine yakın olan taş kolonlar maksimum dikey oturma değerleri vermişlerdir. Artan yük değerlerine bağlı olarak taş kolonların zımbalama göçme değerlerinde artış görülmüştür. Tam ölçekli üç boyutlu analizde taş kolon ile güçlendirilmiş kil katmanında maksimum kabarma taş kolonun çapının üç katı bir derinliğinde meydana gelmektedir.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2012. Supervisor: Assoc. Prof. Dr. Zalihe Nalbantoğlu.
Keywords: Soils--Measurement - Engineering; Axisymmetric Unit Cell - Bulging Failure - Punching Failure - Stone Column - Sand Column - Static and Dynamic Loading